Wnt Genes in Wing Pattern Development of Coliadinae Butterflies - Fenner, Jennifer; Benson, Caleb; Rodriguez-Caro, Luis; Ren, Anna; Papa, Riccardo; Martin, Arnaud; Hoffmann, Federico; Range, Ryan; Counterman, Brian A. (Frontiers in Ecology and Evolution, 2020)
Wnt genes are major developmental genes highly conserved across all animals. Yet, our understanding of the Wnt gene repertoire and their functions is still largely incomplete. In Lepidoptera, Wnt genes have been implicated in wing pattern development. For example, WntA has been shown as a driver of wing pattern diversification in nymphalid butterflies. In this study we characterize the Wnt gene repertoire in Zerene cesonia (Family: Pieridae), which diverged from nymphalids ~51 million years ago, to determine if Wnt genes may have a conserved role in wing development across distant butterfly lineages. We first show that Wnt gene content is highly conserved across butterflies, but that there is strikingly different expression across the eight Wnt genes during wing development of Z. cesonia and nymphalid butterflies. Surprisingly, while four Wnt genes (Wnt1, 6, 7 and 11) are expressed during wing development in Z. cesonia, the renown nymphalid wing patterning gene WntA was undetected. However, despite the differences in Wnt gene expression, Heparin injections yielded a similar disruption in wing color pattern development in both Z. cesonia and nymphalid butterflies. Interestingly, these assays also resulted in the loss of structurally-based ultraviolet wing patterns in Z. cesonia. Collectively, the study shows that pierids maintained the highly conserved nature of Wnt gene content in Lepidoptera, but might deploy these genes very differently from nymphalid butterflies during wing pattern development.